ASSESSMENT OF DROUGHT TOLERANCE IN SOME COTTON GENOTYPES BASED ON DROUGHT TOLERANCE INDICES - A. Ullah; A. Shakeel; T. A. Malik; M. F. Saleem (Journal of Animal and Plant Sciences, 2019)
The limited water supply for irrigation is a major constraint to cotton production. Various drought tolerance indices calculated on the basis of yield provide useful information for drought tolerance. The present study was conducted for the evaluation of nine indices related to drought tolerance, such as stress tolerance index (STI), yield index (YI), stress susceptibility index (SSI), mean productivity (MP), yield stability index (YSI),  relative drought index (RDI), tolerance index (TOL),  sensitive drought index (SDI) and relative decrease in yield index (RDY) in cotton (Gossypium hirsutum L.) genotypes. To accomplish this, forty cotton genotypes were evaluated under two moisture regime i.e. normal and drought stress (50% reduced irrigation) in field by using split plot design under RCBD. The calculation of drought tolerance indices were done on the basis of seed cotton yields both under normal and drought stress condition. All the genotypes behaved differently under two moisture levels. The interaction of cotton genotypes with two environments (moisture levels) were studied for various indices related to drought tolerance on the basis of seed cotton yield using Principle Component Analysis (PCA). The drought tolerant and sensitive genotypes were selected on the basis of biplot analysis. Results revealed that for most of the drought tolerance indices under studied; the genotypes VH-144, IUB-212, MNH-886, VH-295, IR-3701, AA-802, NIAB-111, NS-121, FH-113, and FH-142 are either stable or showing positive interaction with drought conditions. These genotypes can be used in further breeding program for developing varieties suitable for cultivation under drought conditions whereas; IR-3, CIM-443, FH-1000, MNH-147, S-12 interacted undesirably with drought stress.
Keywords: Breeding program; Drought tolerance indices; Gossypium hirsutum L.; Seed cotton yield; Stable